Sustainability science a multidisciplinary approach - Komiyama, Hiroshi 1944- (Sustainability science series, 2011)
Sustainability science is an academic discipline that emerged in response to threats to the sustainability of the global environment. Its purpose is to help build a sustainable society by developing solutions to climate change, the exhaustion of resources, ecological destruction and other environmental crises that threaten the future of humanity. Sustainability science demands a realignment of existing academic disciplines. Whereas academia has fragmented into discrete fields of in-depth specialization, sustainability science seeks comprehensive, integrated solutions to complex problems and a restructuring of education and research that spans multiple disciplines. This volume offers approaches to the development of a transdisciplinary perspective that embraces natural, social and human sciences in the quest for a sustainable society.--Publisher's description.